2022
DOI: 10.1007/s10461-022-03764-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Reasons for Late Presentation to HIV Care in Uganda Among Men and Women

Abstract: Late presentation to HIV care, i.e., presenting with < 200 CD4 cells/mL, is associated with higher mortality and worse outcomes. Despite that, a quarter of people living with HIV in Uganda still present late to care. We surveyed Ugandans living with HIV who enrolled in clinic ≤ 90 days prior. We compared groups who presented 'late' with CD4 < 200 and 'early' with CD4 > 350, stratifying by sex. We found men who presented late had higher externalized stigma than early presenters. Thirty-six percent of the entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…There are currently minimal incentives for early HIV testing, a lack of adequate knowledge and awareness on the frequency of routine HIV testing in the general population, and lack of timely access to HIV testing services. In a qualitative study conducted in Uganda, Lofgren et al 28 also reported participant perceived personal health influences when late presenters sought HIV care; with all late presenters waiting until they were ill and symptomatic before seeking care. This study further confirms the influence personal health perception has on when individuals seek care, with those who are asymptomatic perceiving themselves to be still healthy and therefore seeing no need for HIV care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are currently minimal incentives for early HIV testing, a lack of adequate knowledge and awareness on the frequency of routine HIV testing in the general population, and lack of timely access to HIV testing services. In a qualitative study conducted in Uganda, Lofgren et al 28 also reported participant perceived personal health influences when late presenters sought HIV care; with all late presenters waiting until they were ill and symptomatic before seeking care. This study further confirms the influence personal health perception has on when individuals seek care, with those who are asymptomatic perceiving themselves to be still healthy and therefore seeing no need for HIV care.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study recently conducted in Uganda also highlights alternative therapies including local cures as a reason for delayed HIV care. 28 It is worth noting that all participants reported having accessed HIV-related health education messages including HIV testing but were not motivated to heed these messages. This may point to the quality of HIV testing information and services that are available; there is a need to improve such messages so that they have the desired effect.…”
Section: Discussionmentioning
confidence: 99%
“…HIV is a pandemic infection that affects every part of the globe. According to the International AIDS Vaccine Initiative (IAVI) report, there are a total of 40 million HIV-infected persons in the world, and of these 28.5 million are found in Sub-Saharan Africa [21][22][23][24][25][26][27][28][29][30]. In Africa, adherence to ART is still low [31][32][33][34][35][36].…”
Section: Adherencementioning
confidence: 99%
“…However, stigmatization and discrimination are found to be obstacles to effective ART adherence [19][20][21].…”
Section: Adherencementioning
confidence: 99%